Collins primary focus: comprehension Introductory pupil book - Jackman, John; Evans, Steve (Collins / Peak London /Karachi, 2014)
Collins Primary Focus: Comprehension Introductory Pupil Book is aimed at ages 6+. Using a variety of well-known authors, the book is designed to encourage children to read and understand every essential fiction and non-fiction text type. Follow-up activities progress from literal questions to higher order thinking skills.